2011
DOI: 10.1007/s00125-011-2086-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variants for susceptibility to obesity with type 2 diabetes in Japanese individuals

Abstract: Aims/hypothesis In populations of East Asian descent, we performed a replication study of loci previously identified in populations of European descent as being associated with obesity measures such as BMI and type 2 diabetes.Methods We genotyped 14 single nucleotide polymorphisms (SNPs) from 13 candidate loci that had previously been identified by genome-wide association meta-analyses for obesity measures in Europeans. Genotyping was done in 18,264 participants from two general Japanese populations. For SNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 49 publications
6
45
0
1
Order By: Relevance
“…In this regard, it should be noted that from a clinical point of view, the categorization of a genetic score into a dichotomous variable could be more useful for clinical decision making (Horne et al 2005). The analyses demonstrated that the GRS as a continuous variable predicts \1 % of the BMI variation (0.16 %) in concordance with most of previous studies (Li et al 2010a;Takeuchi et al 2011;Peterson et al 2011;Lemas et al 2013). Nevertheless, our GRS explained 1.59 %.…”
Section: Discussionsupporting
confidence: 73%
“…In this regard, it should be noted that from a clinical point of view, the categorization of a genetic score into a dichotomous variable could be more useful for clinical decision making (Horne et al 2005). The analyses demonstrated that the GRS as a continuous variable predicts \1 % of the BMI variation (0.16 %) in concordance with most of previous studies (Li et al 2010a;Takeuchi et al 2011;Peterson et al 2011;Lemas et al 2013). Nevertheless, our GRS explained 1.59 %.…”
Section: Discussionsupporting
confidence: 73%
“…Li et al (2010) included 12 SNPs that explained 0.9 % of BMI variation in Europeans, Takeuchi et al (2011) calculated a GRS with 14 SNPs that explained 0.65 % among Japanese, and Peterson et al (2011) included 56 SNPs explained 0.66 % of the variation in BMI among a mixed sample of European-and African-Americans. We calculated a GRS in this study using 5 obesity GWAS SNPs that overlap with Li et al (2010), 7 obesity GWAS SNPs that overlap with Takeuchi et al (2011), and 9 obesity GWAS SNPs that overlap with Peterson et al (2011). Taken together, these results suggest that while considerable progress has been made in gene discovery, obesity SNPs highly replicated in GWAS do not yet predict a significant proportion of the heritability attributed to adiposity phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…21 Takeuchi et al reported that rs48454344, which is in almost complete linkage disequilibrium with rs6548238 and rs7561317, 21 was associated with body mass index and type 2 diabetes. 31 Therefore, rs6548238 and rs7561317 in the TMEM18 gene might be susceptible for the development of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Takeuchi et al 31 reported that the G-allele is a risk factor for obesity and is protective for type 2 diabetes. Although further investigations would be necessary, there is a possibility that there are some variations that are specifically associated with components of metabolic syndrome, apart from obesity.…”
Section: Discussionmentioning
confidence: 99%